Osteofibrous dysplasia-like adamantinoma: A case report and literature review - Li, Jian-Wei; Miao, Lei; Zhao, Zhen-Guo; Yang, Lin; Shi, Zhuo; Li, Meng (Frontiers in Oncology, 2022)
Abstract Background: Osteofibrous dysplasia-like adamantinoma (OFD-like adamantinoma), classical adamantinoma and dedifferentiated adamantinoma were previously considered to be three subtypes of adamantinoma of long bones. In the 5th edition of the World Health Organization (WHO) classification of bone tumors in 2020, OFD-like adamantinoma was newly proposed and classified as an intermediate-locally aggressive tumor in other mesenchymal tumors of bone. OFD-like adamantinoma is rare, accounting for only 0.4% of all primary bone tumors. OFD-like adamantinoma is often misdiagnosed due to the insufficient understanding about it. Here we report a case of OFD-like adamantinoma treated in our hospital with a literature review. Case Presentation: The patient, a 14-year-old male, had swelling in his right leg with intermittent pain for one year. Plain film radiography computed tomography (CT) and magnetic resonance imaging (MRI) were performed. Based on the radiological and histological examinations, a diagnosis of OFD-like adamantinoma was suspected. After admission, the patient underwent tumor resection of the right tibia, free transplantation of the left fibula and internal fixation. After resection of the tumor, the wound recovered well, the vital signs were stable, and activity was normal. The patient has been followed up for more than a year with no recurrence or distant metastasis. Conclusion: OFD-like adamantinoma is a rare primary bone tumor with nonspecific clinical features. Imaging examination can demonstrate the lesion and help diagnosis. The pathological discovery of epithelioid tissue is the key evidence for diagnosis.